The Festivities of St. Barbara, St. Ignatius – the God Bearer and Nativity Eve in the Area of the Town of KratovoPraznovanja sv. Barbare, sv. Ignaca - Božje rojstvo in božični večer v okolici mesta Kratovo - Svetieva, Aneta (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">On the bases of the empirical material we can conclude that the New Year’s Eve festivities and rituals begin in the period of the winter solstice, on the day of St. Barbara (4th of December in the Old Style Calendar) and St.Ignatius (20th of December in the Old Style Calendar), when the women from the older generations perform some magical actions in the agrarian rituality. These days are in direct relation with the agrarian character and the folk calendar. They denote the turnover of the trace of the Sun, a period when according to the folk beliefs the sun rises again in the sky and the day becomes longer. During the festivity of the nativity eve the women symbolically show all the phases of the agrarian activity through magic rituals, which initiate good atmospheric influences for the vegetation and the welfare on all the levels. Because of this they give to the fire a vegetative sacrifice from raw, holy tree (oak), cereal sacrifice (ritual breads), a plough (as substitute for the plowing and the fruitfulness), there is symbolical ritual sowing (with a mash of different cereals), they communicate with magic oral formulas etc.